Seroprevalence of Brucellosis in Camels in Bikaner and nearby Villages in Thar Desert of Rajasthan - Saxena, Neharika (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Brucellosis is a hideous illness of camels in India. It is caused by Brucella melitensis and Brucella abortus. The main symptoms of this disease in camels are hygroma and orchitis. Seroprevalence of Brucellosis was studied by RBPT and ELISA. A total of 177 blood samples were collected from camels, aged from 0.2 to 20 years (108 males and 69 females), from Thar Desert of Rajasthan (India). Overall prevalence rate of 8.47% (11/177) and 2.25% (4/177) was observed by RBPT and ELISA, respectively. Variable prevalence was observed age-wise as well as sex-wise. The highest prevalence was observed in the camel more than 12 years of age and the lowest in camels aged 8-12 years. ELISA results indicated prevalence of 3.22% (2/62) in the 5-8 years age group and 1.85 (1/54) in camels aged 8-12 years and over 12 years. This investigation highlights the presence of Brucellosis among camels in Bikaner and surrounding areas of Rajasthan, underlining its zoonotic potential and the associated public health risk for individuals exposed to infected animals, raw milk, or meat.